(untitled) - Louw, Zirk Walter Eon

The toccatas in the Italian lute and theorbo repertoires of the early seventeenth century: a contribution to the history of instrumental music in the beginning of the Baroque (Stellenbosch : Stellenbosch University, 2019)
Thesis (PhD (Music))--Stellenbosch University, 2019